Efficient mixed-domain analysis of electrostatic MEMS - Li, Gang; Aluru, N. R. (Digest of technical papers - IEEE/ACM International Conference on Computer-Aided Design, 2002)
We present efficient computational methods for scattered point and meshless analysis of electrostatic microelectromechanical systems (MEMS). Electrostatic MEMS are governed by coupled mechanical and electrostatic energy domains. A self-consistent analysis of electrostatic MEMS is implemented by combining a finite cloud method based interior mechanical analysis with a boundary cloud method based exterior electrostatic analysis. Lagrangian descriptions are used for both mechanical and electrostatic analyses. Meshless finite cloud and boundary cloud methods combined with fast algorithms and Lagrangian descriptions are flexible, efficient and attractive alternatives compared to conventional finite element/boundary element methods for self-consistent electromechanical analysis. Numerical results are presented for an electrostatic comb drive device.